2009
DOI: 10.1084/jem.20082492
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CTLA-4 on both effector and regulatory T cell compartments contributes to the antitumor activity of anti–CTLA-4 antibodies

Abstract: Cytotoxic T lymphocyte–associated antigen 4 (CTLA-4) is a critical negative regulator of immune responses. Uniquely among known inhibitory receptors, its genetic ablation results in a fulminating and fatal lymphoproliferative disorder. This central regulatory role led to the development of antibodies designed to block CTLA-4 activity in vivo, aiming to enhance immune responses against cancer. Despite their preclinical efficacy and promising clinical activity against late stage metastatic melanoma, the critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
589
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 832 publications
(613 citation statements)
references
References 36 publications
17
589
0
7
Order By: Relevance
“…However, not all its regulatory effects are explained by inhibitory costimulation, since CTLA-4 can also suppress activated effector T-cell populations without the need for them to express it [9,10]. This latter, cell-extrinsic mechanism has been largely attributed to CD4 + regulatory T (Treg)-cell subsets, which constitutively express high levels of CTLA-4, and require it for their regulatory function [11][12][13][14][15][16].…”
Section: Abstract: Cd4 + T Cells R Costimulatory Molecules R Immune Rmentioning
confidence: 99%
“…However, not all its regulatory effects are explained by inhibitory costimulation, since CTLA-4 can also suppress activated effector T-cell populations without the need for them to express it [9,10]. This latter, cell-extrinsic mechanism has been largely attributed to CD4 + regulatory T (Treg)-cell subsets, which constitutively express high levels of CTLA-4, and require it for their regulatory function [11][12][13][14][15][16].…”
Section: Abstract: Cd4 + T Cells R Costimulatory Molecules R Immune Rmentioning
confidence: 99%
“…The discovery of CD4 þ Foxp3 þ Tregs that express high levels of CTLA-4 on their surface, however, suggested a different cellular target for the a-CTLA-4 antibodies-the Tregs themselves (7,8). More recent studies have shown that the blockade of CTLA-4 on both T-effector cells and Tregs is required for optimal tumor immunity (9), and at least in cases in which tumors contain large numbers of macrophages that express Fcg receptors, a-CTLA-4 antibodies seem to mediate the specific depletion of tumor-infiltrating Tregs via an Fc-dependent mechanism (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Moreover, evidences of modification of the balance between effector and regulatory immune responses, involving myeloid derived suppressor cells (MDSCs) and regulatory T cells (Treg), both in the circulation and in tumor infiltrates were reported in association with the clinical activity of IPI. 2,17,18 Along this line, the increase of the absolute leukocyte cell count (ALC) or of circulating CD4 C T cells expressing the inducible co-stimulatory molecule (ICOS) have been documented in relation with anti-CTLA-4 mAb therapies. 12,[19][20][21] ICOS C T cells that were augmented by IPI therapy in tumor lesions from prostate cancer patients, represented lymphocytes endowed with antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These agents showed durable clinical benefit and increased OS, 3,4 for patients with advanced melanoma. Since then, the usage of anti-CTLA-4 mAbs (either ipilimumab, IPI or tremelimumab) in several clinical studies or in the context of expanded access programs (EAP) has shown significant increase in OS for MM patients, and promising clinical activity for tumors with other histology.…”
Section: Introductionmentioning
confidence: 99%